Mapa ou esquema de seta: Qual modalidade os motoristas preferem para sistemas de navegação e guia de rota em automóvel? - Pugliesi, Edmur A. [UNESP]; Decanini, Mônica M.S. [UNESP] (My University, 2009)
This paper intends to study the subjective preference on map and turn-by-turn modalities for In-Car Navigation System and Route Guidance. Twenty eight drivers (14 male and 14 female) took part in a driving simulation. They navigated in an unknown area and were guided by a navigation system that displayed map and turn-by-turn, separately. After the simulation, thee drivers were asked to answer their subjective preference for both modalities, according to the tasks of maneuver direction and route following. The results indicate that most of drivers prefer map and this factor corroborates the previous research.
Map or turn-by-turn: Which modality do the drivers prefer for in-car route guidance and navigation systems?
Keywords: Map; Route guidance and navigation system; Subjective preference; Turn-by-turn